GEO RELIGION: MAPPING PESANTREN AS TAFAQQUH FI AL-DIN USING BUFFERING & NEAREST NEIGHBOR ANALYSIS METHOD (CASE STUDY: TASIKMALAYA REGENCY) - Ai Sulastri; Cindy Dwi Putri Setiady; Lia Berliana; Rahman Firmansyah; Syaefunnisa Syaefunnisa; Rindu Fajar Islamy (Tarbiyah Islamiyah)
This research has two main objectives: to map the locations of pesantren (Islamic boarding schools) in Tasikmalaya City using Geographic Information Systems (GIS) and to analyze their distribution patterns. The study employs Buffer Analysis and Nearest Neighbor Analysis (NNA). Buffer Analysis assesses the accessibility of pesantren, while NNA identifies spatial distribution patterns. The results of NNA show that the distribution of pesantren tends to be clustered in certain areas, influenced by factors such as proximity to religious facilities, large Muslim communities, and easy access for students. Buffer Analysis reveals that 23% of Tasikmalaya City’s area lies within a 1 km radius of a pesantren, indicating good accessibility in several sub-districts. The findings provide important insights for the development of policies in Islamic religious education, including the planning of new pesantren and the optimization of existing facilities. The research emphasizes the role of spatial analysis in improving the accessibility and development of pesantren in the region.